문화적 양극화, 탈북자 토크쇼, 정체성 혼란 -<이제 만나러 갑니다>와 <모란봉 클럽>에 대한 담화 및 담론 분석 - 강민경; 백선기; 남시호; Kang, Min-Kyung; Baek, Seon-Gi; Nam, Siho (한국콘텐츠학회 논문지, 17(1), 2017)
This study investigated formats and structure of meanings for the TV talk shows with North Korean defectors. The authors selected <Now on my way to meet you> of Channel A and <Moran Hill Club> of TV Chosun as research subjects. As results of this study, it was found that the former dealt with heavy issues about North Korea, expressed positive perspectives on North Korea and fantasic expectations about South Korea, and produced superior dicourse of South Korea. On the other hand, the latter one dealt with light and sensational items about North Korea, employed dialogues about critics and disappointments on South Korea, and produced problematic discourse about South Korea. The former produced a kind of converged discourse structure to create superior ideology of South Korea, while the latter produced a kind of dichotomous discourse structure to create frustrating ideology. In short, through this study, it turned out that North Korean defectors suffered from their confused identities, unclear self identities, and minority positions in the South Korean society. 본 연구는 탈북자 TV 토크쇼가 어떠한 포맷과 의미구조를 근간으로 하는지 분석했다. 채널A의 <이제 만나러 갑니다>와 TV조선의 <모란봉 클럽>을 연구대상으로 선정해 탈북자들의 남 북에 대한 사고와 그에 따른 담론 생성에 주목했다. 분석 결과, <이제 만나러 갑니다>는 무거운 주제들과 체제에 대한 주제들을 근간으로 '북한에 대한 긍정형'과 '남한에 대한 판타지형' 담화가 주로 전개되었고, 남한의 우월성을 강조하는 것으로 드러났다. 이에 반해 <모란봉 클럽>은 가볍고 선정적인 주제를 중심으로 '남한에 대한 비판형'과 '남한에 대한 불만형' 담화 유형이 주룰 이루며, 남한의 사회적 문제에 대한 북한의 비판적 시각을 부각시켰다. 또한 <이제 만나러 갑니다>는 수렴적 담론 구조를 근간으로 남한 우월 이데올로기가 두드러진 반면에, <모란봉 클럽>은 대립적인 담론 구조를 통해 남한 절망 이데올로기를 생성하고 있다. 요컨대 한국사회에서 '이방인'으로 분류되는 탈북자들의 혼재된 정체성이 드러났고, 자신들을 반-북한적인 존재로 자임하고 있음과 동시에 남한사회의 정착과정에서 불만 및 혼란스러움을 토로하고 있다.